Literature Review: Potensi Buah Okra (Abelmoschus Esculentus (L) Moench) Sebagai Antidiabetes - AGGRIDITA AGITA PASARIBU; AMANDA AMALIA; VIVI ALYSA ANANDA TAMPUBOLON; SUDANA FATAHILLAH PASARIBU (UNIVERSITAS NGUDI WALUYO, 2022)
Diabetes mellitus is a non-communicable disease characterized by high blood glucose levels. The prevalence of people with diabetes mellitus has increased every year in adults. Okra fruit (Abelmoschus Esculentus) is an herbal plant that is high in fiber and contains flavonoids as antioxidants that have potential as antidiabetic. The purpose of this study was to examine and analyze how big the role of okra fruit as an antidiabetic. This research method is a literature review using a narrative with a search using Google Scholar published between 2010 and 2021 with the keywords